Nanopatterns of arylene–alkynylene squares on graphite: self-sorting and intercalation - Keller, Tristan J.; Bahr, Joshua; Gratzfeld, Kristin; Schönfelder, Nina; Majewski, Marcin A.; Stępień, Marcin; Höger, Sigurd; Jester, Stefan-S. (Beilstein Journal of Organic Chemistry, 2019)
Supramolecular nanopatterns of arylene–alkynylene squares with side chains of different lengths are investigated by scanning tunneling microscopy at the solid/liquid interface of highly oriented pyrolytic graphite and 1,2,4-trichlorobenzene. Self-sorting leads to the intermolecular interdigitation of alkoxy side chains of identical length. Voids inside and between the squares are occupied by intercalated solvent molecules, which numbers depend on the sizes and shapes of the nanopores. In addition, planar and non-planar coronoid polycyclic aromatic hydrocarbons (i.e., butyloxy-substituted kekulene and octulene derivatives) are found to be able to intercalate into the intramolecular nanopores.
Keywords: macrocycles; scanning tunneling microscopy; self-assembled monolayers; self-sorting; solid/liquid interface

(untitled) - Cupo, A.; Masih Das, P.; Chien, C.-C.; Danda, G.; Kharche, N.; Tristant, D.; Drndić, M.; Meunier, V. (ACS Nano, 2017)

(untitled) - Liu, K.; Lihter, M.; Sarathy, A.; Caneva, S.; Qiu, H.; Deiana, D.; Tileli, V.; Alexander, D. T. L.; Hofmann, S.; Dumcenco, D.; Kis, A.; Leburton, J.-P.; et al. (Nano Lett., 2017)

(untitled) - Watt, F.; Bettiol, A. A.; van Kan, J. A.; Teo, E. J.; Breese, M. B. H. (Int. J. Nanosci., 2005)

Handbook of Nanofabrication - Wiederrecht, G. (Academic Press, 2009)

Nanomanufacturing Handbook - Busnaina, A. (CRC Press, 2006)

(untitled) - Böttcher, A.; Heil, M.; Stürzl, N.; Jester, S.-S.; Malik, S.; Pérez-Willard, F.; Brenner, P.; Gerthsen, D.; Kappes, M. M. (Nanotechnology, 2006)

(untitled) - Iritani, K.; Tahara, K.; De Feyter, S.; Tobe, Y. (Langmuir, 2017)

(untitled) - Griessl, S. J. H.; Lackinger, M.; Jamitzky, F.; Markert, T.; Hietschold, M.; Heckl, W. M. (Langmuir, 2004)

(untitled) - Korolkov, V. V.; Baldoni, M.; Watanabe, K.; Taniguchi, T.; Besley, E.; Beton, P. H. (Nat. Chem., 2017)

(untitled) - Lackinger, M.; Griessl, S.; Heckl, W. M.; Hietschold, M.; Flynn, G. W. (Langmuir, 2005)

(untitled) - Kampschulte, L.; Lackinger, M.; Maier, A.-K.; Kishore, R. S. K.; Griessl, S.; Schmittel, M.; Heckl, W. M. (J. Phys. Chem. B, 2006)

(untitled) - Liao, L.-y.; Li, Y.-b.; Xu, J.; Geng, Y.-f.; Zhang, J.-y.; Xie, J.-l.; Zeng, Q.-d.; Wang, C. (J. Phys. Chem. C, 2014)

(untitled) - Iyoda, M.; Yamakawa, J.; Rahman, M. J. (Angew. Chem., Int. Ed., 2011)
Iyoda, M.; Yamakawa, J.; Rahman, J. Angew. Chem. 2011, 123, 10708–10740. doi:10.1002/ange.201006198

(untitled) - Liu, C.; Park, E.; Jin, Y.; Liu, J.; Yu, Y.; Zhang, W.; Lei, S.; Hu, W. (Angew. Chem., Int. Ed., 2018)
Liu, C.; Park, E.; Jin, Y.; Liu, J.; Yu, Y.; Zhang, W.; Lei, S.; Hu, W. Angew. Chem. 2018, 130, 1887–1891. doi:10.1002/ange.201711040

(untitled) - Schmaltz, B.; Rouhanipour, A.; Räder, H. J.; Pisula, W.; Müllen, K. (Angew. Chem., Int. Ed., 2009)
Schmaltz, B.; Rouhanipour, A.; Räder, H. J.; Pisula, W.; Müllen, K. Angew. Chem. 2009, 121, 734–738. doi:10.1002/ange.200803156

(untitled) - Adisoejoso, J.; Tahara, K.; Okuhata, S.; Lei, S.; Tobe, Y.; De Feyter, S. (Angew. Chem., Int. Ed., 2009)
Adisoejoso, J.; Tahara, K.; Okuhata, S.; Lei, S.; Tobe, Y.; De Feyter, S. Angew. Chem. 2009, 48, 7489–7493. doi:10.1002/ange.200900436

(untitled) - Liu, C.; Park, E.; Jin, Y.; Liu, J.; Yu, Y.; Zhang, W.; Lei, S.; Hu, W. (Angew. Chem., Int. Ed., 2018)
Liu, C.; Park, E.; Jin, Y.; Liu, J.; Yu, Y.; Zhang, W.; Lei, S.; Hu, W. Angew. Chem. 2018, 130, 9122–9126. doi:10.1002/ange.201803937

(untitled) - Jester, S.-S.; Sigmund, E.; Höger, S. (J. Am. Chem. Soc., 2011)

(untitled) - Wilhelm, P.; Vogelsang, J.; Poluektov, G.; Schönfelder, N.; Keller, T. J.; Jester, S.-S.; Höger, S.; Lupton, J. M. (Angew. Chem., Int. Ed., 2017)
Wilhelm, P.; Vogelsang, J.; Poluektov, G.; Schönfelder, N.; Keller, T. J.; Jester, S.-S.; Höger, S.; Lupton, J. M. Angew. Chem. 2017, 129, 1254–1258. doi:10.1002/ange.201610723

(untitled) - Yang, T.; Berber, S.; Liu, J.-F.; Miller, G. P.; Tománek, D. (J. Chem. Phys., 2008)

(untitled) - Ilan, B.; Florio, G. M.; Hybertsen, M. S.; Berne, B. J.; Flynn, G. W. (Nano Lett., 2008)

(untitled) - Yin, S.; Wang, C.; Qiu, X.; Xu, B.; Bai, C. (Surf. Interface Anal., 2001)

(untitled) - Xu, L.; Yang, L.; Lei, S. (Nanoscale, 2012)

(untitled) - Hu, Y.; Miao, K.; Xu, L.; Zha, B.; Miao, X.; Deng, W. (RSC Adv., 2017)

(untitled) - Adisoejoso, J.; Tahara, K.; Lei, S.; Szabelski, P.; Rżysko, W.; Inukai, K.; Blunt, M. O.; Tobe, Y.; De Feyter, S. (ACS Nano, 2012)

(untitled) - Wu, A.; Isaacs, L. (J. Am. Chem. Soc., 2003)

(untitled) - Majewski, M. A.; Hong, Y.; Lis, T.; Gregoliński, J.; Chmielewski, P. J.; Cybińska, J.; Kim, D.; Stępień, M. (Angew. Chem., Int. Ed., 2016)
Majewski, M. A.; Hong, Y.; Lis, T.; Gregoliński, J.; Chmielewski, P. J.; Cybińska, J.; Kim, D.; Stępień, M. Angew. Chem. 2016, 128, 14278–14282. doi:10.1002/ange.201608384

(untitled) - Gaefke, G.; Höger, S. (Synthesis, 2008)

(untitled) - Glaser, C. (Ber. Dtsch. Chem. Ges., 1869)

(untitled) - Siemsen, P.; Livingston, R. C.; Diederich, F. (Angew. Chem., Int. Ed., 2000)
Siemsen, P.; Livingston, R. C.; Diederich, F. Angew. Chem. 2000, 112, 2740–2767. doi:10.1002/1521-3757(20000804)112:15<2740::AID-ANGE2740>3.0.CO;2-F

(untitled) - Giancarlo, L. C.; Flynn, G. W. (Annu. Rev. Phys. Chem., 1998)

(untitled) - Ghijsens, E.; Ivasenko, O.; Tahara, K.; Yamaga, H.; Itano, S.; Balandina, T.; Tobe, Y.; De Feyter, S. (ACS Nano, 2013)

(untitled) - Kaneda, Y.; Stawasz, M. E.; Sampson, D. L.; Parkinson, B. A. (Langmuir, 2001)

(untitled) - Tahara, K.; Balandina, T.; Furukawa, S.; De Feyter, S.; Tobe, Y. (CrystEngComm, 2011)

(untitled) - Sleczkowski, P.; Dappe, Y. J.; Croset, B.; Shimizu, Y.; Tanaka, D.; Minobe, R.; Uchida, K.; Lacaze, E. (J. Phys. Chem. C, 2016)

(untitled) - Samorí, P.; Severin, N.; Simpson, C. D.; Müllen, K.; Rabe, J. P. (J. Am. Chem. Soc., 2002)

Carbon Materials and Nanotechnology - Krüger, A. (Wiley-VCH, 2010)

(untitled) - Chari, T.; Ribeiro-Palau, R.; Dean, C. R.; Shepard, K. (Nano Lett., 2016)

Encyclopedia of Interfacial Chemistry – Surface Science and Electrochemistry - Holtsch, A.; Uder, B.; Hartmann, U. (Moiré Patterns of Graphene and Their Local Density of States, 2018)

(untitled) - Hu, Y.; Bragança, A. M.; Verstraete, L.; Ivasenko, O.; Hirsch, B. E.; Tahara, K.; Tobe, Y.; De Feyter, S. (Chem. Commun., 2019)

(untitled) - Inokuma, Y.; Arai, T.; Fujita, M. (Nat. Chem., 2010)